Fertility awareness and parenting intentions among Mexican undergraduate and graduate university students. (15th March 2022) - Place, J. M.; Peterson, B.D.; Horton, B.; Sanchez, M.
Abstract: An online, cross-sectional survey was carried out between November 2017 and January 2018 to assess fertility awareness among students attending the National Autonomous University of Mexico (UNAM) in Mexico City. A total of 371 students participated in the survey ( n  = 228 females, 143 males). 75% of females and 74% of males believed a woman's fertility begins to decline markedly after age 40. Over 75% of all participants overestimated the probability of couples having a live birth after undergoing one cycle of IVF. With regard to parenting intentions, only 48% of females wished to have children compared to 59% of males ( p  = 0.037) and men were more likely to have their first child at age 30 or later (71% men vs 55% women). In the event of infertility, participants had a higher preference not to have children or to pursue adoption rather than use in vitro fertilisation (IVF). In summary, university students in Mexico City demonstrated low levels of fertility awareness and a smaller proportion indicated a wish to have children than has been reported by young people elsewhere in the world.